Superinfection occurs in Anaplasma phagocytophilum infected sheep irrespective of infection phase and protection status - Stuen, Snorre (BioMed Central, 2009)
BACKGROUND: Anaplasma phagocytophilum infection in domestic ruminants is widespread in the coastal areas of southern Norway. The bacteria may persist in mammalian hosts. Several genetic variants of A. phagocytophilum exist. In the present study, we investigate whether superinfection occurs in the acute and persistent phase of the infection. METHODS: Five-month-old lambs of the Norwegian Dala breed were experimentally infected with two 16S rRNA gene variants of A. phagocytophilum, i.e. A. phagocytophilum variant 1 (GenBank accession number M73220) and variant 2 (GenBank acc. no. AF336220). Eighteen lambs were used, two lambs in each group. Eight groups were experimentally inoculated with either variant 1 or 2 on day 0. Six of these groups were then challenged with the other variant on either days 7, 42 or 84, respectively. One group was left uninfected. The occurrence of A. phagocytophilum in blood samples was determined using semi-nested PCR analysis and gene sequencing. Specific antibodies were measured by an indirect immunofluorescence antibody assay (IFA). RESULTS: A. phagocytophilum variant 1 and 2 differed significantly with regards to clinical reaction and cross-immunity in infected lambs. Both variants were found in the blood after challenge. However, variant 1 was detected most frequently. CONCLUSION: The present experiment indicates that superinfection of different genotypes occurs during the acute as well as the persistent phase of an A. phagocytophilum infection, even in lambs protected against the challenged infection.